Evidence of the role of prosody in argumentative writing: Comma use in texts written by Brazilian students aged 11-14 - Soncin, Geovana [UNESP]; Tenani, Luciani Ester [UNESP] (Equinox Publishing Ltd, 2017)
This paper aims to provide a linguistic analysis of prosodic patterns (especially the complex of suprasegmental phonological features which includes intonation, pauses and stress) underlying use of commas in texts written by Brazilian students. The analysed material consists of texts produced in the last year of primary education at a public school in an inner city of Sao Paulo State, Brazil. The object of analysis is composed of two kinds of comma use which occur in a simple scheme: unconventional uses and conventional uses of commas, both uses being defined from grammatical rules taught at school. The analysis leads to a theoretical discussion about the importance of orality in the way people approach writing and the relationship between orality and writing in text production practices at school. It is argued that accounting for the relationship between orality and literacy may reveal linguistic phenomena and important symbolic processes which are identifiable in the writing of young students who are going through the learning process of writing texts at school.
Keywords: WRITING TEXT; JUNIOR HIGH SCHOOL; BRAZILIAN PORTUGUESE; PROSODY; PUNCTUATION